Cognitive biases in pediatric cardiac care - Padovani, Paul; Roy, Arnaud; Guerra, Amanda; Cadeau, Olivier; Ly, Mohamed; Vasile, Corina M.; Pass, Robert H.; Baruteau, Alban-Elouen (Frontiers in Cardiovascular Medicine, 2024)
Medical practitioners are entrusted with the pivotal task of making optimal decisions in healthcare delivery. Despite rigorous training, our confidence in reasoning can fail when faced with pressures, uncertainties, urgencies, difficulties, and occasional errors. Day-to-day decisions rely on swift, intuitive cognitive processes known as heuristic or type 1 decision-making, which, while efficient in most scenarios, harbor inherent vulnerabilities leading to systematic errors.Cognitive biases receive limited explicit discussion during our training as junior doctors in the domain of paediatric cardiology. As pediatric cardiologists, we frequently confront emergencies necessitating rapid decision-making, while contending with the pressures of stress, fatigue, an earnest interest in 'doing the right thing' and the impact of parental involvement. This article aims to describe cognitive biases in pediatric cardiology, highlighting their influence on therapeutic interventions for congenital heart disease. Whether future pediatric cardiologists or experienced professionals, understanding and actively combating cognitive biases are essential components of our ongoing medical education. Furthermore, it is our responsibility to thoroughly examine our own practices in our unwavering commitment to providing high-quality care.Cognitive biases have been identified in all steps of decision making (13-15), including information gathering, association triggering, context formulation, processing and verification (16). The diagnostic enterprise, construed as the distinctive characterisation of a specific disease or